Bidirectional cyclical flows increase energetic costs of station holding for a labriform swimming fish, Cymatogaster aggregata. Issue 1 (19th August 2020) - Luongo, Sarah M; Ruth, Andreas; Gervais, Connor R; Korsmeyer, Keith E; Johansen, Jacob L; Domenici, Paolo; Steffensen, John F
Abstract: Wave-induced surge conditions are found in shallow marine ecosystems worldwide; yet, few studies have quantified how cyclical surges may affect free swimming animals. Here, we used a recently adapted respirometry technique to compare the energetic costs of a temperate fish species ( Cymatogaster aggregata ) swimming against a steady flow versus cyclical unidirectional and bidirectional surges in which unsteady swimming (such as accelerating, decelerating and turning) occurs. Using oxygen uptake ( Ṁ O2 ) as an estimate of energetic costs, our results reveal that fish swimming in an unsteady (i.e. cyclical) unidirectional flow showed no clear increase in costs when compared to a steady flow of the same average speed, suggesting that costs and savings from cyclical acceleration and coasting are near equal. Conversely, swimming in a bidirectional cyclical flow incurred significantly higher energetic costs relative to a steady, constant flow, likely due to the added cost of turning around to face the changing flow direction. On average, we observed a 50% increase in Ṁ O2 of fish station holding within the bidirectional flow (227.8 mg O2 kg −1 h −1 ) compared to a steady, constant flow (136.1 mg O2 kg −1 h −1 ) of the same mean velocity. Given wave-driven surge zones are prime fish habitats in the wild, we suggest the additional costs fish incur by station holding in a bidirectional cyclical flow must be offset by favourable conditions for foraging and reproduction. With current and future increases in abiotic stressors associated with climate change, we highlight the importance of incorporating additional costs associated with swimming in cyclical water flow in the construction of energy budgets for species living in dynamic, coastal habitats.